44-7*x-3=13

Simple and best practice solution for 44-7*x-3=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 44-7*x-3=13 equation:


Simplifying
44 + -7x + -3 = 13

Reorder the terms:
44 + -3 + -7x = 13

Combine like terms: 44 + -3 = 41
41 + -7x = 13

Solving
41 + -7x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-41' to each side of the equation.
41 + -41 + -7x = 13 + -41

Combine like terms: 41 + -41 = 0
0 + -7x = 13 + -41
-7x = 13 + -41

Combine like terms: 13 + -41 = -28
-7x = -28

Divide each side by '-7'.
x = 4

Simplifying
x = 4

See similar equations:

| m+2m-2m-m+3m=15 | | 3x-5=11x-56 | | 9x-1=-X+9 | | 3x^2+x=x | | X+(180-x)+105+75=360 | | 2x(x-2)=3(x+2) | | 4(f+1)= | | (4x-2)+(x+28)=180 | | 6x+7x+8x=42 | | 4y-7=x+28 | | 150x=28500 | | -1.7=2x | | 6x-1=16+3x | | (x-5)=18 | | 3x+ax+b=-3 | | 45x=30(40) | | 4x=5(5) | | (-4-4x)/(x^2-x-2) | | C(30)=30 | | y=0.4x+2 | | 8*2x+6=10(x+6) | | t/9−7=−5 | | y=0.7x+2 | | 4(x+3)=7+4x | | (x-iy)(3-4i)=3-29i | | 3x+6=6(x-1)-3x | | 5X+4-6=2 | | -2(-6-7n)+5=145 | | 5*3x+8=4(25) | | 25-[2+9y-3(y+5)]=-4(4y-7)-[8(y-1)-15y+22] | | -6p+8p=16+4p | | 1.3(-2)-5.6= |

Equations solver categories